1992
DOI: 10.1007/bf00944189
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of gemcitabine in advanced colorectal adenocarcinoma

Abstract: A phase II trial of gemcitabine (difluorodeoxycytidine) was conducted in 14 patients with advanced colorectal adenocarcinoma. Gemcitabine was administered intravenously over 30 minutes at weekly intervals for 3 consecutive weeks each month. The starting dose was 800 mg/m2, with dose escalation as tolerated. No complete or partial response were observed. Ten patients experienced progressive disease while on therapy. Toxic effects were primarily hematologic in nature. Grade 3 toxicities included leukopenia (one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 14 publications
0
16
1
Order By: Relevance
“…The incorporation of gemcitabine into DNA increases oxaliplatin binding to DNA, and this may explain the synergistic activity of the combination. In phase II studies of patients with advanced CRC, gemcitabine monotherapy has shown minimal activity [17, 18]. In an attempt to improve treatment results, Mani et al [33] have tested a longer infusion duration of 150 min, but this proved ineffective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of gemcitabine into DNA increases oxaliplatin binding to DNA, and this may explain the synergistic activity of the combination. In phase II studies of patients with advanced CRC, gemcitabine monotherapy has shown minimal activity [17, 18]. In an attempt to improve treatment results, Mani et al [33] have tested a longer infusion duration of 150 min, but this proved ineffective.…”
Section: Discussionmentioning
confidence: 99%
“…Gemcitabine monotherapy has been registered as standard treatment of pancreatic cancer and proved active in other malignancies including lung, urothelial, breast and ovarian cancer. In advanced CRC, however, gemcitabine alone has minimal activity [17, 18]. …”
Section: Introductionmentioning
confidence: 99%
“…head and neck cancer (Braakhuis et al, 1991), colorectal cancer (Moore et al, 1992) and non-small cell lung cancer (Lilenbaum et al, 1993). However, no large clinical trial…”
Section: Introductionmentioning
confidence: 99%
“…It has also shown preclinical and clinical activity in several other solid tumours, including ovarian, head and neck and breast cancers (Carmichael et al, 1995;Markman, 2002). However, phase I/II trials of single-agent gemcitabine have not demonstrated any activity in advanced colorectal and gastric cancers (Moore et al, 1992;Christman et al, 1994;Mani et al, 1998). We therefore wished to test this combination on further gastrointestinal tumour samples and investigate any schedule dependency.…”
mentioning
confidence: 99%